2023
DOI: 10.1186/s12917-023-03593-5
|View full text |Cite|
|
Sign up to set email alerts
|

N-thiocarboxyanhydrides, amino acid-derived enzyme-activated H2S donors, enhance sperm mitochondrial activity in presence and absence of oxidative stress

Abstract: Background Hydrogen sulfide (H2S) donors are crucial tools not only for understanding the role of H2S in cellular function but also as promising therapeutic agents for oxidative stress-related diseases. This study aimed to explore the effect of amino acid-derived N-thiocarboxyanhydrides (NTAs), which release physiological H2S levels in the presence of carbonic anhydrase, on porcine sperm function during short-term incubation with and without induced oxidative stress. For this purpose, we employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…It was found that H 2 S-releasing agents based on amino acids simulated the release of physiological levels of H 2 S in the presence of carbonic anhydrase without exerting harmful effects on cell function. In addition, the H 2 S-releasing agents enhanced the forward motility of sperm during short-term treatment, which may prolong the survival of sperm [131]. These results suggest that the regulatory effects of H 2 S on sperm motility in vitro may contribute to assisted reproduction.…”
Section: H 2 S Promotes Male Fertilitymentioning
confidence: 79%
“…It was found that H 2 S-releasing agents based on amino acids simulated the release of physiological levels of H 2 S in the presence of carbonic anhydrase without exerting harmful effects on cell function. In addition, the H 2 S-releasing agents enhanced the forward motility of sperm during short-term treatment, which may prolong the survival of sperm [131]. These results suggest that the regulatory effects of H 2 S on sperm motility in vitro may contribute to assisted reproduction.…”
Section: H 2 S Promotes Male Fertilitymentioning
confidence: 79%
“…A sperm aliquot (2 µL) was loaded into a pre-warmed Leja chamber (Leja Products BV, The Netherlands, chamber depth: 20 µm). The sperm motility and kinetic parameters were evaluated, as previously reported [26], using a Computer Assisted Sperm Analysis (CASA) (NIS-Elements, Nikon, Tokyo, Japan and Laboratory Imaging, Prague, Czech Republic), which consists of an Eclipse E600 tri-ocular phase contrast microscope (Nikon, Tokyo, Japan), equipped with a warming stage set at 38 ºC (Tokai Hit, Shizuoka, Japan), and a DMK 23UM021 digital camera (The Imaging Source, Bremen, Germany). The analysis was carried out using a 10× negative phase-contrast objective (Nikon, Tokyo, Japan).…”
Section: Sperm Motility and Kinetics Parametersmentioning
confidence: 99%
“…The seminal ORP of the samples were determined as previously reported [26] with minor modifications. At the end of sperm incubation, a sample from each treatment was centrifuged at 16, 300 g for 5 minutes at room temperature.…”
Section: Seminal Oxidation-reduction Potential (Orp)mentioning
confidence: 99%
“…Considering the physiological and cytoprotective significance of H 2 S 49 , as well as the functional role of H 2 S donor compounds in biological systems 50 and also in sperm 22 , 29 , 58 to the best of our knowledge, in this study for the first time, we investigate the potential protective capabilities of fast-releasing (NaHS) and slow-releasing (GYY4137) H 2 S donors in maintenance of sperm functional parameters and in vitro fertilization rate in goat species following cryopreservation.…”
Section: Introductionmentioning
confidence: 99%